Stolen : five free boys kidnapped into slavery and their astonishing odyssey home - Bell, Richard, 1978- (New York : 37 INK ; Simon & Schuster, 2019)
"A ... true story about five boys who were kidnapped in the North and smuggled into slavery in the Deep South--and their daring attempt to escape and bring their captors to justice."--
The reverse Underground Railroad -- Sanctuary city -- Black hearts -- Midnight land -- In-laws and outlaws -- The beaten way -- The body in the wagon -- The halfway house -- The lifeboat -- A living witness -- Hunting wolves -- Kidnappers all -- The first law of nature.
Includes bibliographical references and index.
Keywords: Child slaves -- United States -- Biography; Kidnapping victims -- United States -- Biography; Fugitive slaves -- United States -- Biography; African Americans -- Biography; Free African Americans -- Legal status, laws, etc. -- History -- 19th century; Slavery -- United States -- History -- 19th century; United States -- Race relations -- History -- 19th century